Seasonal Variation in the Diversity of the Gut Microbiota of Short‐Faced Moles Reveals the Associations of Climatic Factors on the Gut Microbiota of Subterranean Mammals - Di Xu; Mengmeng Wu; Zenghao Gao; Yue Zhao; Meng Hu; Yang Wen; Linlin Wang; Deli Xu; Lei Chen (Ecology and Evolution)
ABSTRACT The composition of animal gut microbiota is significantly affected by a variety of factors. Seasonal variation in environmental factors is believed to have a significant impact on the composition of mammalian gut microbiota. Therefore, studying the seasonal differences in gut microbiota diversity in wildlife is of great importance to explore their ecological adaptability. This study compared the diversity of gut microbiota of the short‐faced moles (Scaptochirus moschatus) in spring, summer, and autumn by using 16S rRNA amplification sequencing. Our results reveal significant seasonal differences in the diversity and function of the short‐faced moles gut microbiota. Compared to spring, the diversity and function of the gut microbiota in summer and autumn of short‐faced moles are more similar to each other. The relative abundance of Firmicutes is higher in spring than in summer and autumn, while the relative abundance of Proteobacteria in summer and autumn is higher than that of spring. There are significant differences in carbohydrate metabolism between spring and summer, and between spring and autumn. The correlation analysis results suggest that climatic factors are strongly associated with seasonal variation in gut microbiota of the short‐faced moles, especially temperature and relative humidity. The present study discusses the seasonal variations in the gut microbiota diversity of short‐faced moles and the significant impact of climatic factors on gut microbiota diversity. These results will highlight the potential impact of climatic factors on the seasonal changes of the gut microbiota of subterranean mammals and provide a new view for comprehensively understanding the ecological adaptation of subterranean mammals.